Identification of Intestinal Fungal Microflora and Bacterial Pathogens in the Collected Adult Ixodes ricinus from the Northern Provinces of Iran - Manijeh Yousefi Behzadi; Neda Moazzezy; Mehdi Rohani; Saied Reza Naddaf; Ehsan Mostafavi; Ali Mohamadi; Masoomeh Shams-Ghahfarokhi; Nasrin Pashootan; Mehdi Razzaghi-Abyaneh (Tehran University of Medical Sciences, 2023)
Background: Ticks are vectors of many pathogens that involve various important diseases in humans and animals, they have several diverse hosts consequently can retain a diverse group of indigenous microbes, from bacteria to fungi. Little is known about the prevalence and diversity of tick microflora colonizing the midgut and their effects on ticks and their interaction. This information is important for development of vector control strategies. Methods: This study was carried out in northern Iran during autumn 2019. Ticks, Ixodes ricinus caught alive on the bodies of domestic animals in the fall. The tick homogenate was prepared. The identification of fungal isolates was carried out according to a combination of macro and microscopic morphology and molecular sequencing. Pathogenic bacteria of the family Borreliaceae, Francisella tularensis, Borrelia burgdorferi and Coxiella burnetii were tested by real-time PCR. Results: A total of 133 mature I. ricinus ticks were collected from domestic animals, including 71.5% cattle and 28.5% sheep. The tick frequency rates were 87.21% for Mazandaran, 8.28% for Golestan and 4.51% for Gilan Provinces. Total prevalence of fungal tick contamination was 53.4% (75/133) of which Trichoderma harzianum (57%) was the most prevalent species followed by Aspergillus spp. (42%), Mortierella alpine (19%) and Penicillium polonicum (14%). All tick samples were negative for three pathogenic bacteria including Francisella tularensis, Coxiella burnetii, and Borrelia burgdorferi by real-time PCR analysis. Conclusion: These results show a first picture of the microbial diversity of ticks and highlight the importance of microbiota and their role in host-pathogen interaction.